Evaluation of green wall in the decrease of noise and its environmental perception in an educational center - Zeballos Pimentel, Ana Claudia (2020)
The study aimed to install a green wall in order to carry out a comparative analysis of the levels of noise reduction, as well as to evaluate the environmental perception; the study was carried out in the city of Tacna in the facilities of the educational institution Verdad y Vida - Veritas et Vita. For the construction of the green wall, the Aptenia cordifolia that was installed outside the educational center was used. In order to noise reduction monitoring, two monitoring points were located; one in the direction of the noise source and the other behind the green wall where the noise is directed. Monitoring was carried out at night and daytime, resulting in a reduction in daytime of 2,593 ± 0.47 and at night of 5.38 ± 0.19 in both cases significant (p-value -0.05). The environmental perception evaluated by the student population indicates that 50% perceive that green walls reduce noise. It is concluded that green walls can reduce noise and that they could serve as an acoustic screen, with Aptenia cordifolia being a good alternative.